Bridging the Generation Gap: The Reality of EMR Implementation. (2nd September 2014) - Garcia‐Rodriguez, Laura R.; Singer, Michael C.; Ko, Alvin B.
Abstract : Objectives: Assess the attitude of academic otolaryngology faculty members toward a new electronic medical record (EMR) and determine the impact of implementation on their perspectives. Methods: A longitudinal survey study was conducted from December 2013 to June 2013 at an academic medical center. All otolaryngology and audiology faculty members were serially administered an online, 10‐question survey assessing their attitudes toward implementation of a new EMR system. These surveys were completed 3 months prior and 1 and 3 months after implementation. Basic demographic information was also collected. Results: Thirty faculty members completed all 3 surveys. Compared with respondents over 40 years old, those under 40 years reported being more comfortable with computers ( P =. 035). Prior to implementation, respondents under 40 years were statistically more likely to believe that the new EMR documentation would be both more efficient ( P =. 018) and higher quality ( P =. 030). However, by the end of the study the attitudes of the groups had converged; those under 40 years were less positive about the efficiency and quality of documentation in the new system and those over 40 years had become more enthusiastic about these aspects of EMR documentation. Conclusions: Younger faculty members appear to be more comfortable with the use of computers. This possibly led them to be more optimistic about the potential benefits of the EMR system. However, implementation appeared to alter both age cohorts' perspectives, with younger faculty becoming less positive and older faculty becoming more enthusiastic about the EMR's impact.